(3eUGHjM GdSfIs - (3GdMSjf Hf eSYhO Hf eMeO GdHZhj , GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, (B510 (3g`s ((3CHh HcQ Hf Ydj GdUhajhj GdMfajs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai bGd GdTjN GdEeGe CHh eMeO GdMSjf Hf eSYhO GdaQGA GdHZhj GeG HYO agPg CdaGX UOQJ Yf UOQ GdfHhI hSff SGQJ Yf eYOf GdQSGdI hCMGOjK LGAJ Yf SjO GdeQSdjf hNGJe GdfHjjf ef eUGHjM GdOLi NQLJ ef eTcGI GdJbhi eeG GhQOgG GdCFeI aj cJHges
(3BNQgG (B:s
(3Yf CHj gQjQI Cf GdfHj Udi Gddg Ydjg hSde bGd (B: " (3hOOJ Cfj QCjJ ENhGffG bGdhG (B: (3jG QShd Gddg CSfG ENhGfc bGd Udi Gddg Ydjg hSde (B: (3Hd GfJe CUMGHj hENhGffG GdPjf de jCJhG ef HYO hCfG aQWge Ydi GdMhV ef GdMjGf Yf CfS QVj Gddg JYGdi Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: "(3eKd CeJj eKd GdeWQ dG jOQj Chdg NjQ Ce BNQg (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 259s
(3eYLe GdeDdajf (B1 / 644s
(3cTa GdXfhf (B2 / 1698s
(3TPQGJ GdPgH (B4 / 48s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs